Outcome after cytoreductive surgery combined with hyperthermic intrathoracic chemotherapy in patients with secondary pleural metastases - Hassan, Mohamed; Zimmermann, Julia; Schmid, Severin; Passlick, Bernward; Kovács, Julia; Hatz, Rudolf; Winter, Hauke; Klotz, Laura V.; Eichhorn, Martin E.; Markowiak, Till; Müller, Karolina; Huppertz, Gunnar; et al. (Frontiers in Oncology, 2023)
The role of cytoreductive surgery combined with hyperthermic intrathoracic chemotherapy (CRS+HITOC) for patients with secondary pleural metastases has scarcely been investigated. Patients and Methods: We conducted a retrospective, multicenter study investigating the outcome of CRS+HITOC for 31 patients with pleural metastases from different primary tumours in four high-volume departments of thoracic surgery in Germany. The primary endpoint was overall survival (OS). Secondary endpoints included postoperative complications and recurrence/progression-free survival (RFS/PFS). Results: The primary tumour was non-small cell lung cancer in 12 (39%), ovarian cancer in 5 (16%), sarcoma in 3 (10%), pseudomyxoma peritonei in 2 This is a provisional file, not the final typeset article 3 (10%), and others in 8 (26%) patients. A macroscopic complete resection (R/1) could be achieved in 28 (90%) patients. Major postoperative complications as classified by Clavien-Dindo (III-V) were observed in 11 (35%) patients. The postoperative mortality rate was 10% (n=3). A total of 13 patients received additive chemotherapy (42%). The median time of follow up was 30 months (95% CI = 17-43). The median OS was 39 months (95% CI: 34-44 months) with 1-month, 3-month, 1-, 3-, and 5year survival estimates of 97%, 89%, 77%, 66%, and 41%. There was a significantly prolonged OS in patients who received additive chemotherapy compared to patients with only CRS+HITOC (median OS 69 vs 38 months; p= 0.048). The median RFS was 14 months (95% CI: 7-21 months). Conclusions: We observed that CRS+HITOC is a feasible approach with reasonable complications and prolonged survival as a part of multimodal concept for highly selected patients with secondary pleural metastases.